2018
DOI: 10.1371/journal.pone.0193254
|View full text |Cite
|
Sign up to set email alerts
|

Tree cover and species composition effects on academic performance of primary school students

Abstract: Human exposure to green space and vegetation is widely recognized to result in physical and mental health benefits; however, to date, the specific effects of tree cover, diversity, and species composition on student academic performance have not been investigated. We compiled standardized performance scores in Grades 3 and 6 for the collective student body in 387 schools across the Toronto District School Board (TDSB), and examined variation in relation to tree cover, tree diversity, and tree species compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 29 publications
2
55
0
3
Order By: Relevance
“…The most promising findings for the influence of green space on achievement were for college preparatory exams results; of eight total findings, seven (88%) showed beneficial associations between green space and achievement [48,60]. Moreover, we found exclusively positive associations between college exams and green land cover or tree cover at all distances [28,54,55,60,61]. End-of-semester grades also showed exclusively positive associations for green window views and trees in up to 250 m distances away from schools [48,60].…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…The most promising findings for the influence of green space on achievement were for college preparatory exams results; of eight total findings, seven (88%) showed beneficial associations between green space and achievement [48,60]. Moreover, we found exclusively positive associations between college exams and green land cover or tree cover at all distances [28,54,55,60,61]. End-of-semester grades also showed exclusively positive associations for green window views and trees in up to 250 m distances away from schools [48,60].…”
Section: Resultsmentioning
confidence: 84%
“…Our analysis of methodological biases showed that the majority of the included studies ( n = 9) were of fair quality [28,48,49,52,53,55,59,60,61]. Only two were of good [58] or excellent quality [51], and two more were of poor quality [47,54].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, several studies in the US have revealed a positive association between school and neighborhood greenness and children's academic attainment, although previous studies exploring this relationship did not differentiate between different types of greenery (i.e., tree, shrub and grass) . More recent studies by Sivarajah, Smith, & Thomas (2018) and Kuo, Browning, Sachdeva, Lee and Westphal (2018) positively link school tree cover density with academic achievement.…”
Section: School Ground Design and Academic Attainmentmentioning
confidence: 94%